A review paper on R&D efforts in assessing the traffic noise on highways - Vij, G S; Agrawal, M L (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">In rapidly urbanizing country like India, the transportation sector is growing in a fast pace and the number of vehicles on Indian roads is increasing at a rate of more than 7% per annum. This has led to over crowded roads and pollution. Transportation sector is one of the major contributors to noise in urban area, which contributes 55% of total noise on highway. In view of this, it is essential to study highway noise with respect to various causative factors. Hence, various noise prediction models have been developed, throughout the world to assess its impact on to the society and the human beings. These traffic noise prediction models differ in some respects, but the overall methodology is similar. All the noise prediction models consists of evaluating basic noise levels and making series of adjustments to take into account geometric, traffic flow, barrier data etc. In this paper, noise prediction models of U.S.A. and U.K. (FHWA and CORTON) along with the research efforts on noise in Indian context has been studied and discussed.